Photoperiod and initial ontogeny of migratory fish in Brazil with special emphasis on sabalo (Prochilodus lineatus) - Hernández Cuadrado, Ever Edrey (2016)
The study of reproductive aspects and ontogeny of migratory fish is relevant in pisciculture, especially when it is related to native species, emphasizing the patterns of growth and development of these taxa. The present research aimed to make a compilation of current knowledge on the ontogeny of sabalo, Prochilodus lineatus, in embryonic and larval stages, under varying photic environments and the adaptive capacity of the phenotype. Besides, the cases of other species currently cultivated or potentially productive in this stages were reviewed. Thus, the manipulation of light and darkness regimes has allowed to move forward or backwards the onset of reproduction and improve growth rates, as well as the embryonic and larval development in fish. Nevertheless, data is dispersed and in some cases there are information gaps, especially on migratory fish species in Brazil, including the sabalo. In this compilation, the modulating action of some environmental factors such as photoperiod, which can be manipulated to improve the production of sabalo in the early stages of its life cycle is highlighted. By the nature of these factors, efforts should be addressed from the perspective of adaptation or phenotypic plasticity of the studied biological model.